Why Do Family-controlled Firms Donate to Charity? The Role of Intrafamily Succession Intention, Social Status, and Religiosity. (20th July 2015) - Li, Weiwen; Au, Kevin Yuk-fai; He, Ai; Song, Lihong
ABSTRACT: Drawing on expectancy theory and the socioemotional wealth (SEW) perspective, we propose that family owners with intrafamily succession intention are more motivated to accumulate or preserve SEW. As corporate philanthropy is a critical way for family-controlled firms to accumulate or maintain SEW, family owners with intrafamily succession intention are more likely to engage in corporate philanthropic activities. Data on a nationally representative sample of family-controlled firms in China support our prediction. We also find that the relationship between intrafamily succession intention and corporate philanthropy is moderated by family owners' social status and religiosity. The findings contribute to our understanding about family businesses, in general, and those in China, in particular, as well as the SEW perspective.